2011
DOI: 10.1159/000331311
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Breast Health Awareness amongst Women in an Urban Slum Area in Alexandria, Egypt

Abstract: Background: Breast Cancer (BC) is the most frequently occurring cancer among Egyptian women. This study aimed to determine the effectiveness of a health education program on raising the knowledge related to BC, its risk factors, and some related preventive practices among women living in an urban slum area in Alexandria. Patients and Methods: A pre-/post-test interventional study was conducted during 2009–2010 on a random sample of women aged 30–65 years (n = 486) living in a slum area in Alexandria, Egypt. 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Our results concur with findings of other educational interventions conducted within the US, including those in Northern[28] and Southern[29] California, Florida[30], Massachusetts and Georgia[19], NYC and Arkansas[9], Texas[6, 31], and North Carolina[32] as well as international studies[5, 10, 12]. Our educational tools consisted of Power Point presentations delivered in lectures catered to each participating group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results concur with findings of other educational interventions conducted within the US, including those in Northern[28] and Southern[29] California, Florida[30], Massachusetts and Georgia[19], NYC and Arkansas[9], Texas[6, 31], and North Carolina[32] as well as international studies[5, 10, 12]. Our educational tools consisted of Power Point presentations delivered in lectures catered to each participating group.…”
Section: Discussionsupporting
confidence: 90%
“…Our educational tools consisted of Power Point presentations delivered in lectures catered to each participating group. Previous studies utilized a variety of interventions including presentations, seminars or workshops[5, 6, 9, 10, 28], focused discussion groups[30], video breast health kits[19], and culturally targeted booklets[6, 12, 29, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the posttest of the present study demonstrated significant improvements in students' performance of BSE, which is certainly attributed to the practical part of the program. The effectiveness of the program in improving the practice of BSE is in agreement with a number of studies from several countries as in China (Ouyang and Hu, 2014), Ghana (Mena et al, 2014), the United States (Zeinomar and Moslehi, 2013) as well as in Alexandria, Egypt (Kharboush et al, 2011). …”
Section: Discussionsupporting
confidence: 85%
“…Operational definition used by municipal authorities to define slum is 'Residential areas characterized by being developed in contradiction to planning and building laws and regulations in the absence of state's supervision [3] . The research studies in Egypt for health assessment of slum dwellings are scares: some are related to child health [4] , whereas others are related to maternal health [5,6] . Most urban residents in sub-Saharan Africa live in slums often characterized by a lack of basic services such as water and sewerage.…”
Section: Introductionmentioning
confidence: 99%